Microencapsulamento por spray dryer de antocianinas e polifenois de jussara (Euterpe edulis Martius) e incorporação em sistemas-modelo de bebidas lácteas - Lima, Emília Maria França (2016)
The color is a sensory attribute that has great influence on the acceptance of a product, being necessary to use colorants for food with attractive colors. Anthocyanins are natural pigments that give attractive colors and potentially beneficial to health, being present in large quantities in jussara, fruit of Euterpe edulis Martius palm. However, they present instability to some technological processes, making them difficult to use in large scale. Microencapsulation is an alternative to improve the stability of the pigment and facilitate its incorporation into products. This work aimed to evaluate the addition of microencapsulated anthocyanins in model systems of dairy beverages. The microcapsules were obtained by spray drying with different encapsulating agents (maltodextrin, gum arabic and inulin) and outlet air drying temperatures (50, 55, 60, 65 and 70 °C) and evaluated for retention of anthocyanins, compounds phenolics, antioxidant activity, water activity, hygroscopicity, wettability, moisture, color, scanning electron microscopy (SEM) and X-ray diffraction. The desirability statistical tool was used to define the optimum conditions for obtaining powders having desirable characteristics. Powders produced in these conditions (maltodextrin and temperature air outlet 50 °C) were incorporated into the milk beverage model systems, evaluating the stability of their bioactive compounds against the time and different storage package. It was found that the microcapsules obtained with maltodextrin at 50 °C, gum arabic at 70 °C and inulin at 70 °C showed the most desirable characteristics (maximization of anthocyanins retention, phenolic content and antioxidant activity, and reduction of hygroscopicity and immersion time), whereas treatment with maltodextrin showed the highest desirability. SEM and X-Ray diffraction proved the efficiency microencapsulation by observing spherical capsules of uniform size and an amorphous structure. It was concluded that it is feasible to extract and incorporate microencapsulated anthocyanins of jussara in dairy beverages, each anthocyanin content remained constant (p> 0.05) for the two kinds of beverage stored in opaque and transparent packages. Furthermore, there was no decay of phenolics and antioxidant activity. The color was observed only a little variation over the 28 days of storage under refrigeration.